High-order accurate finite-volume formulations for the pressure gradient force in layered ocean models. (August 2017) - Engwirda, Darren; Kelley, Maxwell; Marshall, John
Highlights: High-order finite-volume schemes for evaluation of the PGF in layered ocean models. Support for complex, fully non-linear equations-of-state. Support for non-uniform stratification profiles, steeply-sloping coordinate surfaces. Minimse spurious horizontal velocities in terrain-following and isopycnic-type models. Abstract: Discretisation of the horizontal pressure gradient force in layered ocean models is a challenging task, with non-trivial interactions between the thermodynamics of the fluid and the geometry of the layers often leading to numerical difficulties. We present two new finite-volume schemes for the pressure gradient operator designed to address these issues. In each case, the horizontal acceleration is computed as an integration of the contact pressure force that acts along the perimeter of an associated momentum control-volume. A pair of new schemes are developed by exploring different control-volume geometries. Non-linearities in the underlying equation-of-state definitions and thermodynamic profiles are treated using a high-order accurate numerical integration framework, designed to preserve hydrostatic balance in a non-linear manner. Numerical experiments show that the new methods achieve high levels of consistency, maintaining hydrostatic and thermobaric equilibrium in the presence of strongly-sloping layer geometries, non-linear equations-of-state and non-uniform vertical stratification profiles. These results suggest that the new pressure gradient formulations may be appropriate for general circulation models that employ hybrid vertical coordinates and/or terrain-following representations.